Shogun Assassin Based on a Manga-Series by Kazuo Koike and Goseki Kojima - Houston, Robert; Misumi, Kenji; Makiura, Chishi; Wakayama, Tomisaburo; Tomikawa, Akihiro; Ôki, Minoru (The Criterion Collection, 2017)
"Shogun Assassin", known in Japan as "Kozure Ōkami" is a jidaigeki film made for the British and American markets and released in 1980. It was edited and compiled from the first two films in the "Lone Wolf and Cub" series, using 12 minutes of the first film, "Lone Wolf and Cub: Sword of Vengeance", and most of "Lone Wolf and Cub: Baby Cart at the River Styx" ... The project was directed by Robert Houston and his partner David Weisman, a protégé of Andy Warhol and director of "Ciao! Manhattan" (1972). A fan of the original "Kozure Ōkami" films, Weisman had obtained the rights for $50,000 from the American office of Toho Studios. [wikipedia.org]